Linkage of crustal deformation between the Archaean basement and the Proterozoic cover in the Peräpohja Area, northern Fennoscandia - Simo Piippo; Pietari Skyttä; Armelle Kloppenburg (Elsevier, 2022)
Constraints from restoration of minor rift-related faults preserved from subsequent Palaeoproterozoic overprint along the southern margin of the Peräpohja Belt, northern Fennoscandia indicate local NE-SW extension directions prevailed at the time of 2.44 Ga rifting of the Archaean continent. This palaeostress field is attributed to pull-apart setting of the Peräpohja Belt at a left overstepping zone of major sinistral N-S trending deformation zones. Consequently, the variably overprinted NW-SE trending structures of the Peräpohja Belt, including the NW-SE central graben were originally generated as normal faults. The proposed setting is compatible with a conducted reconnaissance sandbox analogue model where the orientation of the major normal faults was controlled by the ambient stress field within the step-over zone between strike-slip faults. By contrast, the faults bounding E-W to ENE-WSW trending basement horsts are the result of reactivation of older basement structures underlying the pull-apart basin. Based on the results, we infer that the final break-up of the Archaean continent in northern Fennoscandia utilized the 2.44 Ga rift-related NW-SE trending crustal anisotropy (parallel with dyke swarms), with pre-existing Archaean N-S trending structures reactivated as second-order shear zones in-between. The voluminous syn-rift 2.5-2.4 Ga and later pulses of mafic magmatism (2.32-1.98 Ga) are considered indicative of active-type rifting which onset was controlled by a mantle plume centred within a supercraton formed by the Superior, Hearne and Karelian (-Kola) cratons. The presented model supports the continuity of the Archaean craton beyond the Caledonian Orogen towards north-west and explains its segmentation, suggesting a model for the localization of the Palaeoproterozoic supracrustal belts of Northern Fennoscandia. Moreover, this paper provides an approach to understand the basement-cover relationships and the structural signatures within these relatively shallow supracrustal belts which are highly prospective for mineral deposits.